The Impact of Digitization on Legal Systems in Developing Countries - Ikhtiyor Djuraev; Azim Baratov; Shokhjakhon Khujayev; Iroda Yakubova; Mokhichekhra Rakhmonova; Bobur Mukumov; Nodirakhon Abdurakhmanova (Qubahan Academic Journal, 2025)
This study investigates the transformative impact of digitization on legal systems in developing countries, emphasizing the integration of emerging technologies such as blockchain and smart contracts. By exploring case studies from India, Kenya, Brazil, Rwanda, South Africa, the Philippines, and Ghana, the research highlights how digital adoption enhances legal infrastructure, expands access to justice, and drives regulatory evolution. A mixed-method approach, combining qualitative interviews and quantitative analysis of legal reforms, reveals that digitization significantly reduces case backlogs, improves transparency, and accelerates judicial processes. However, persistent challenges, including inadequate digital infrastructure, disparities in digital literacy, and cybersecurity vulnerabilities, underscore the need for coordinated interventions. The study identifies blockchain as a critical tool for ensuring the integrity and security of legal records, providing tamper-proof documentation, and fostering trust in legal processes. Similarly, smart contracts streamline legal transactions by automating and enforcing agreements, reducing costs, and enhancing efficiency. These technologies are essential for modernizing judicial frameworks and addressing governance gaps, particularly in regions grappling with corruption and bureaucratic inefficiencies. Ultimately, the findings underscore the importance of phased implementation strategies, investments in digital literacy, and inclusive policy frameworks to maximize the benefits of legal digitization. By integrating blockchain and smart contracts, developing countries can build resilient, transparent, and accessible legal systems that respond to the dynamic needs of their societies.